Iatrogenic dependence of anabolic-androgenic steroid in an Indian non-athletic woman. (6th February 2014) - Tripathi, Adarsh; Tekkalaki, Bheemsain; Saxena, Shashwat; Dandu, Himanshu
Abstract : Anabolic-androgenic steroids (AAS) are increasingly being used by athletes and youngsters to become masculine and to loose body fat. Long-term consumption of AAS causes multiple physical and psychological morbidities. Research has also concluded that AAS have addictive potential and AAS abuse is commonly found with other substance abuse. Abuse of AAS is rare in eastern countries. Abuse among women is even rarer. Here is a case report of an Indian woman, who was prescribed nandrolone decanoate injections by an unqualified medical practitioner to treat multiple non-specific somatic pains and reported weakness, leading to dependence for nandrolonedecanoate. This case report supports the research finding of abuse potential of AAS, raises concern about the need for spreading the awareness about AAS abuse among medical professionals, regulating medical practice by unqualified practitioners, and strict legal check against AAS availability in developing countries.